2011
DOI: 10.1097/bpo.0b013e31820fc620
|View full text |Cite
|
Sign up to set email alerts
|

Digital Avulsion With Compromised Vascularization

Abstract: The global rate of survival after revascularization or replantation of avulsed fingers in children seemed to be poor. Urbaniak classification is an important prognostic factor with a good prognosis for lesions classified as Urbaniak 2 and a very poor prognosis for lesions classified as Urbaniak 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 34 publications
0
21
0
2
Order By: Relevance
“…Отрыв и сдавление дают самые плохие результаты [12]. Изучение серий больных показывает, что шансы на выживание реплантированного пальца после полного отрыва составляют от 25 до 100 % [3,4,7,[13][14][15][16][17][18][19][20], но данные последнего мета-анализа [12] свидетельствуют о 66 % с возрастанием доли выживаемости при трак-ционном отчленении трехфалангового пальца (78 %) в сравнении с первым (68 %). Доля выживаемости паль-цев при неполном тракционном отчленении, по данным этого же исследования, составляет 78 %, в том числе большого пальца -53 % и 87 % -длинных пальцев.…”
Section: степень выживаемости пальцевunclassified
See 1 more Smart Citation
“…Отрыв и сдавление дают самые плохие результаты [12]. Изучение серий больных показывает, что шансы на выживание реплантированного пальца после полного отрыва составляют от 25 до 100 % [3,4,7,[13][14][15][16][17][18][19][20], но данные последнего мета-анализа [12] свидетельствуют о 66 % с возрастанием доли выживаемости при трак-ционном отчленении трехфалангового пальца (78 %) в сравнении с первым (68 %). Доля выживаемости паль-цев при неполном тракционном отчленении, по данным этого же исследования, составляет 78 %, в том числе большого пальца -53 % и 87 % -длинных пальцев.…”
Section: степень выживаемости пальцевunclassified
“…Yan Lefevre et al [20] на серии, включающей 23 слу-чая тракционного отчленения пальцев у детей, сред-ний возраст которых составлял 11 лет (от 2 до 15 лет), получил всего 25 % успешных результатов по восста-новлению кровоснабжения. Согласно исследований Urbaniakа, в группах 2 и 3 выживаемость составила 75 % и 5 % соответственно.…”
Section: степень выживаемости пальцевunclassified
“…When the skin has been physiologically degloved, but is still attached to the body, it can be vascularised by either arterial anastomosis, venous anastomosis or both, as the situation warrants, and this procedure is called revascularisation[45] [Figure 3]. Thus, replacing the degloved part and vascularising it by microvascular anastomosis gives back the patient skin and a soft tissue cover in good quality and quantity.…”
Section: Surgical Optionsmentioning
confidence: 99%
“…Thus, replacing the degloved part and vascularising it by microvascular anastomosis gives back the patient skin and a soft tissue cover in good quality and quantity. [34] Replantation of degloved parts [Figure 4] has got certain unique features…”
Section: Surgical Optionsmentioning
confidence: 99%
“…Few studies exist specifically examining the outcomes of avulsion injuries in children. Lefevre et al performed a retrospective study of 23 children with digital avulsions with compromised vascularity and found that while the survival rate of digits with only partial degloving or amputations was 75 %, the survival of digits with complete degloving or amputations was only 5.3 % [80]. Thus, in children with the most severe avulsion injuries, the likelihood of success with replantation is low.…”
Section: Amputationsmentioning
confidence: 99%